Symbiotic Interactions Between Mosquitoes and Mosquito Viruses - Altinli, Mine; Schnettler, Esther; Sicard, Mathieu (Frontiers in Cellular and Infection Microbiology, 2021)
Mosquitoes not only transmit human and veterinary pathogens called arboviruses (arthropod-borne viruses) but also harbour mosquito-associated insect-specific viruses (mosquito viruses) that cannot infect vertebrates. In the past, studies investigating mosquito viruses mainly focused on highly pathogenic interactions that were easier to detect than those without visible symptoms. However, the recent advances in viral metagenomics have highlighted the abundance and diversity of viruses which do not generate mass mortality in host populations. Over the last decade, this has facilitated the rapid growth of virus discovery in mosquitoes. The circumstances around the discovery of mosquito viruses greatly affected how they have been studied so far. While earlier research mainly focused on the pathogenesis caused by DNA and some double-stranded RNA viruses during larval stages, more recently discovered single-stranded RNA mosquito viruses were heavily studied for their putative interference with arboviruses in female adults. Thus, many aspects of mosquito virus interactions with their hosts and host-microbiota are still unknown. In this context, considering mosquito viruses as endosymbionts can help to identify novel research areas, in particular in relation to their long-term interactions with their hosts (e.g. relationships during all life stages, the stability of the associations at evolutionary scales, transmission routes and virulence evolution) and the possible context-dependent range of interactions (i.e. beneficial to antagonistic). Here, we review the symbiotic interactions of mosquito viruses considering different aspects of their ecology, such as transmission, host specificity, host immune system and interactions with other symbionts within the host cellular arena. Finally, we highlight related research gaps in mosquito virus research.